Effects and cost of different strategies to eliminate hepatitis C virus transmission in Pakistan: a modelling analysis. Issue 3 (March 2020) - Lim, Aaron G; Walker, Josephine G; Mafirakureva, Nyashadzaishe; Khalid, Gul Ghuttai; Qureshi, Huma; Mahmood, Hassan; Trickey, Adam; Fraser, Hannah; Aslam, Khawar; Falq, Gregoire; Fortas, Camille; Zahid, Hassaan; et al.
Summary: Background: The WHO elimination strategy for hepatitis C virus advocates scaling up screening and treatment to reduce global hepatitis C incidence by 80% by 2030, but little is known about how this reduction could be achieved and the costs of doing so. We aimed to evaluate the effects and cost of different strategies to scale up screening and treatment of hepatitis C in Pakistan and determine what is required to meet WHO elimination targets for incidence. Methods: We adapted a previous model of hepatitis C virus transmission, treatment, and disease progression for Pakistan, calibrating using available data to incorporate a detailed cascade of care for hepatitis C with cost data on diagnostics and hepatitis C treatment. We modelled the effect on various outcomes and costs of alternative scenarios for scaling up screening and hepatitis C treatment in 2018–30. We calibrated the model to country-level demographic data for 1960–2015 (including population growth) and to hepatitis C seroprevalence data from a national survey in 2007–08, surveys among people who inject drugs (PWID), and hepatitis C seroprevalence trends among blood donors. The cascade of care in our model begins with diagnosis of hepatitis C infection through antibody screening and RNA confirmation. Diagnosed individuals are then referred to care and started on treatment, which can result in a sustained virological response (effective cure). We report the median and 95% uncertainty interval (UI) from 1151 modelled runs. Findings: One-time screening of 90% of the 2018 population by 2030, with 80% referral to treatment, was projected to lead to 13·8 million (95% UI 13·4–14·1) individuals being screened and 350 000 (315 000–385 000) treatments started annually, decreasing hepatitis C incidence by 26·5% (22·5–30·7) over 2018–30. Prioritised screening of high prevalence groups (PWID and adults aged ≥30 years) and rescreening (annually for PWID, otherwise every 10 years) are likely to increase the number screened and treated by 46·8% and decrease incidence by 50·8% (95% UI 46·1–55·0). Decreasing hepatitis C incidence by 80% is estimated to require a doubling of the primary screening rate, increasing referral to 90%, rescreening the general population every 5 years, and re-engaging those lost to follow-up every 5 years. This approach could cost US8·1 billion, reducing to 3·9 billion with lowest costs for diagnostic tests and drugs, including health-care savings, and implementing a simplified treatment algorithm. Interpretation: Pakistan will need to invest about 9·0% of its yearly health expenditure to enable sufficient scale up in screening and treatment to achieve the WHO hepatitis C elimination target of an 80% reduction in incidence by 2030. Funding: UNITAID.